2012
DOI: 10.1002/jcp.24033
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and proteomic characterization of alkaptonuric chondrocytes

Abstract: Alkaptonuria (AKU) is a rare genetic disease associated with the accumulation of homogentisic acid (HGA) and its oxidized/polymerized products which leads to the deposition of melanin-like pigments (ochronosis) in connective tissues. Although numerous case reports have described ochronosis in joints, little is known on the molecular mechanisms leading to such a phenomenon. For this reason, we characterized biochemically chondrocytes isolated from the ochronotic cartilage of AKU patients. Based on the macroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 48 publications
8
61
0
Order By: Relevance
“…Also, apoptosis might be mediated by a reorganization of the cytoskeleton, which leads to the release of the pro‐apoptotic signal. Actually, we previously observed two different chondrocytic populations isolated from ochronotic AKU cartilage and showing distinct proteomic profiles (Braconi et al, 2012) that could be related to normal and chondrocytes with secretory phenotype here described. In agreement with chondroptosis here reported, proteomics of AKU chondrocytes revealed an over‐expression of programmed cell death 6‐interacting protein (PDC6I) and a profound alteration in the levels of proteins involved in protein folding and cell organization, cytoskeleton integrity, RER‐associated protein catabolic process, RER‐unfolded protein response, retrograde protein transport (RER to cytosol), and protein ubiquitination (Braconi et al, 2012).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Also, apoptosis might be mediated by a reorganization of the cytoskeleton, which leads to the release of the pro‐apoptotic signal. Actually, we previously observed two different chondrocytic populations isolated from ochronotic AKU cartilage and showing distinct proteomic profiles (Braconi et al, 2012) that could be related to normal and chondrocytes with secretory phenotype here described. In agreement with chondroptosis here reported, proteomics of AKU chondrocytes revealed an over‐expression of programmed cell death 6‐interacting protein (PDC6I) and a profound alteration in the levels of proteins involved in protein folding and cell organization, cytoskeleton integrity, RER‐associated protein catabolic process, RER‐unfolded protein response, retrograde protein transport (RER to cytosol), and protein ubiquitination (Braconi et al, 2012).…”
Section: Discussionmentioning
confidence: 53%
“…Our previous work (Braconi et al, 2010,b; Tinti et al, 2010; Tinti et al, 2011a,2011b; Braconi et al, 2012; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Spreafico et al, 2013) suggested that morphological changes of chondrocytes in AKU cartilage may be attributed to apoptosis, but until now no in depth study exists to elucidate if chondroptosis may occur in AKU. Moreover, ultra‐structural observations were complemented with biochemical and proteomic characterization of chondrocytes isolated from the ochronotic cartilage of AKU patients, indicating that AKU chondrocytes are characterized by HGA‐induced apoptosis, protein aggregation, nitric oxide release, and oxidative stress (Tinti et al, 2011a; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Spreafico et al, 2013).…”
mentioning
confidence: 99%
“…A range of human serum-, cell-and tissue-based human models have been established in the last years (schematically depicted in FIGURE 2) [30,[33][34][35]53,[60][61][62][63]. These human AKU models are based on exogenous addition of HGA range concentrations analogous to those found in AKU patients' plasma.…”
Section: Therapy Of Alkaptonuriamentioning
confidence: 99%
“…• Increased apoptosis, nitric oxide (NO) release and levels of pro-inflammatory cytokines in chondrocytes from AKU patients [60].…”
Section: Therapy Of Alkaptonuriamentioning
confidence: 99%
“…AKU patients sometimes suffer from cardiovascular disease (frequent cause of death; Pettit et al, 2011) and kidney disease (Butany et al, 2006). There is no effective cure for AKU at the moment (Braconi, Laschi, Amato et al, 2010;Braconi, Laschi, Taylor et al, 2010;Tinti et al, 2010;Tinti, Taylor et al, 2011;Braconi et al, 2012). Treatment of symptoms is possible, although this is recommended for the early stage of the disease while for the end stage, total joint replacement is required (Tinti, Spreafico et al, 2011).…”
Section: Introductionmentioning
confidence: 99%